A CONSTITUCIONALIDADE DA TIPIFICAÇÃO DOS CRIMES DE PERIGO ABSTRATO COM FOCO NA EMBRIAGUEZ AO VOLANTE - SANTOS, ELLEN (2022)
Criminal Law is governed by the Principle of Minimum Intervention, as it carries more severe sanctions than other fields of law. However, since society is responsible for the valuation of legal assets, expectations of protection are created for their fears and anxieties, the legislator responds with the typification of crimes of abstract danger. Bearing this reality in mind, the objective of this academic research is to analyze the constitutionality of the classification of crimes of abstract danger, with the specific objective of framing the crime of drunk driving, located in article 306 of the Brazilian Traffic Code, as a crime of danger. To achieve these objectives, descriptive and exploratory methods were used; furthermore, this is qualitative research, due to the critical analysis of several doctrinal points of view. For a better understanding of the research, the contents were compartmentalized into three different topics dealing with specific and essential themes for the construction of the general and specific objectives, explaining crime, crimes of harm and danger and an analysis of the article 306. From the analysis of doctrine, jurisprudence, current criminal legislation and the Federal Constitution of 1988, it was found a plurality of points of view regarding the constitutionality of crimes of abstract danger and regarding the framing of the crime of drunk driving as such. With this theoretical basis, the result of the research was formed in the sense that the classification of crimes of abstract danger can indeed be considered constitutional – despite the valid criticisms of the doctrine – as shown by the jurisprudence of the Superior Courts and some Regional Courts. For this reason, it is also correct to frame the type of crime of drunk driving as an abstract danger, as it aims to protect the legal interest “public safety”, with its sanction being evaluated according to the specific case, in order to reconcile its effectiveness with the reasonableness of the penalty in relation to the conduct.